ОГЛЯД ОСНОВНИХ ФАКТОРІВ, ЩО ВПЛИВАЮТЬ НА НАДІЙНІСТЬ МУЛЬТИСЕРВІСНИХ МЕРЕЖ ЗВ’ЯЗКУ - Правило, Валерій Володимирович; Фомін, Микола Миколайович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Peculiarities of distribution of network resources by class of service in multiservice communication network The basic factors that constantly affect the functioning of multiservice networks. As a result of factors are divided into three main groups: technical, programmatic, operational and detailed analysis of each of these group. Disclosed both advantages and disadvantages of the main factors indicated ways to improve the reliability of multiservice communication network.